Tectonic evolution of the eastern margin of the Southern Patagonian Andes fold-thrust belt: U-Pb detrital zircon geochronology and kinematic-structural modelling - Albano Garcia, Juan Francisco (2023)
We present a multidisciplinary study in the Austral-Magallanes basin combining U-Pb geochronology and provenance analysis with structural modelling to unravel the evolution of the fold-thrust belt and related foreland basin sedimentation. Our approach is innovative for the studied area, where the foreland stratigraphic record comprises a stack of marine deposits exceeding 5000 m in thickness. Using zircon U-Pb geochronology from 13 samples distributed through the foreland deposits in the Southern Patagonian Andes at 51°20′S latitude, we calculated maximum depositional ages and analyzed regional variations in provenance. The older sample, with an age of 96.0 ± 1.5 Ma, corresponds to the first sandstone beds of the Punta Barrosa Formation, whereas the uppermost sample, with an age of 17.9 ± 0.4 Ma stems from the Santa Cruz Formation. Furthermore, the presented data help to complete the geochronological information existing for the South Patagonian Andes, by informing the regional geodynamic framework and timing variations. Linking new and previously published data regarding detrital zircon provenance, maximum depositional ages analysis, thermochronology and stratigraphic data with a balanced structural cross section, we propose a step-by-step model combining the kinematic evolution of the fold-thrust belt orogenic front with the basin history. A wedge-top setting for the Late Cretaceous is recognized, as well as two minor uplift events by Eocene time, followed by a major Miocene tectonic exhumation event.